Recruitment, data collection, participation rate, and representativeness of the international cross-sectional PRICOV-19 study across 38 countries - Tatsioni, Athina; Groenewegen, Peter; Van Poel, Esther; Vafeidou, Kyriaki; Assenova, Radost; Hoffmann, Kathryn; Schaubroeck, Emmily; Stark, Stefanie; Tkachenko, Victoria; Willems, Sara (BMC Primary Care, 2023)
Background: Recruitment for surveys has been a great challenge, especially in general practice. Methods: Here, we reported recruitment strategies, data collection, participation rates (PR) and representativeness of the PRICOV-19 study, an international comparative, cross-sectional, online survey among general practices (GP practices) in 37 European countries and Israel. Results: Nine (24%) countries reported a published invitation; 19 (50%) had direct contact with all GPs/GP practices; 19 (50%) contacted a sample of GPs /GP practices; and 7 (18%) used another invitation strategy. The median participation rate was 22% (IQR = 10%, 28%). Multiple invitation strategies (P-value 0.93) and multiple strategies to increase PR (P-value 0.64) were not correlated with the PR. GP practices in (semi-) rural areas, GP practices serving more than 10,000 patients, and group practices were over-represented (P-value < 0.001). There was no significant correlation between the PR and strength of the primary care (PC) system [Spearman’s r 0.13, 95% CI (-0.24, 0.46); P-value 0.49]; the COVID-19 morbidity [Spearman’s r 0.19, 95% CI (-0.14, 0.49); P-value 0.24], or COVID-19 mortality [Spearman’s r 0.19, 95% CI (-0.02, 0.58); P-value 0.06] during the three months before country-specific study commencement. Conclusion: Our main contribution here was to describe the survey recruitment and representativeness of PRICOV-19, an important and novel study.
CRIS-Team Scopus Importer:2024-12-16
Keywords: COVID-19; Family medicine; PRICOV-19 study; Primary health care; Quality of care; Recruitment; Representativeness